Coping mechanisms of widows in Brgy. Can-adieng, Ormoc City - Sacay, Dennis (1998)
Coping mechanisms among widows was investigated. Including their parenting style and the effects on their children. There were five (5) respondents. Each one of them were informed about the nature of the interview. They were only five (5) because nowadays they are very scarce. This study aims to answer the following: coping mechanisms of widows and the corresponding effects on the children. The method used was the interview technique and the naturalistic observation. After giving a thorough analysis of widows coping mechanisms, parenting style and effects on children the researcher has found out that widows have shown a remarkable adaptiveness and coping skills in the face of stress. Furthermore, this study was conducted in Brgy. Can-adieng, Ormoc City.